Penjaga Terakhir Kebudayaan: Strategi Bisnis dan Keredaksian Majalah Djaka Lodang dalam Melestarikan Budaya Jawa - Alip Kunandar; Qonita Hukaimah (Universitas Ahmad Dahlan, 2020)
Document from the Linguistics Department of University of Indonesia records that there are 742 regional languages in Indonesia. From that number, only 13 regional languages are spoken by no more than one million people. The most disconcerting problem is that many regional languages are threatened with extinction and some have even become extinct or no speakers are found. This happens for various reasons, and one of the influences that cannot be ignored is mass media. The mass media in Indonesia, both print and electronic, generally use Bahasa Indonesia as a medium of communication. On the other hand, the use of Bahasa Indonesia as the medium of instruction in mass media contributes to the transfer of Indonesian as the language of unity, but on the other hand, this has eradicated the use of regional languages.Another thing of concern is the lesser number of mass media that use local languages as the medium of instruction. Djaka Lodang Magazine is one of the printed mass media using regional languages that remain still in Indonesia, besides Mangle, Penjebar Semangat, and Jayabaya. The magazine, which was published in Yogyakarta since 1971, experienced a golden period during the 1980-1990s, but then it continued to decrease and nearly bankrupt like any other printed media since the development of communication technology which erodes the older media.However, although this media is no longer profitable in business selling, Djaka Lodang still survives and is published today. One of the main factors that made this magazine survive is bold support of the idealism of its founder, who is still active until today. Abdullah Purwodarsono, one of the owners of this magazine, has a strongdetermination to continue publishing Djaka Lodang, for the sake of one main goal, to keep and preserve the Javanese language and culture, an effort that has mutualism with the function of the press, i.e. the transmission of cultural heritage. This article will discuss the business and editorial strategy of Djaka Lodang magazine that makes this magazine survive in the midst of major changes in the world of media and the changes of language and culture in Indonesia.